Use of symbiotics in ventilator-associated pneumonia prophylaxis - Sainz-Rueda, Nestor Alejandro (2012)
INTRODUCTION: Ventilator-associated pneumonia (VAP) is particularly important in the intensive care unit where they increase in morbidity, mortality and cost. AIMS: To investigate the effect of a mixture of probiotics and fructooligosaccharides (Lactofos®) on the incidence of ventilator-associated pneumonia in patients in mechanical ventilation compared to a use of fructooligosaccharides (FOS) alone (Fiberfos®) MATERIAL AND METHODS: It was a prospective, randomized, double blind, placebo controlled trial performed in a Brazilian teaching hospital. Adult patients expected to be in mechanical ventilation for up to 48 h received probiotics (Lactobacillus paracasei Lpc-37, Lactobacillus rhamnosus HN001, Lactobacillus acidophilus NCFM, Bifidobacterium lactis HN019) in gastro-intestinal and oropharyngeal sites plus fibers twice a day or FOS alone. RESULTS: The two groups (n=125) were comparable at baseline and received comparables cares except for the use of probiotics. Probiotic group (n=62) was twice less likely to develop VAP than compared to the group that received only prebiotics (41.3% vs. 20.9 %, P = 0.011). Probiotic group also had fewer days of hospitalization (23.1 days vs.18.5 days, P = 0.024). The mortality did not differ significantly between the groups CONCLUSIONS: The use of Lactofos® reduced length of hospitalization and ventilator-associated pneumonia incidence compared to Fiberfos® but had no statistically significant impact on mortality.